Female Sex Workers' Experiences with Intended Pregnancy and Antenatal Care Services in Southern Tanzania. Issue 1 (March 2015) - Beckham, Sarah W.; Shembilu, Catherine R.; Brahmbhatt, Heena; Winch, Peter J.; Beyrer, Chris; Kerrigan, Deanna L.
<x xml:space="preserve">Abstract</x> Understanding the pregnancy experiences of female sex workers (FSWs), especially in the context of high rates of HIV and sexually transmitted infections (STIs), is essential to tailoring services to meet their needs. This study explores FSWs' experiences with intended pregnancy and access to antenatal care and HIV testing in two regions of Tanzania. Thirty in‐depth interviews and three focus group discussions were conducted. FSWs sought to become pregnant to gain respect as mothers, to avoid stigma, and/or to solidify relationships, sometimes posing risks to their own and their partners' health. Pregnant FSWs generally sought antenatal care (ANC) services but rarely disclosed their occupation, complicating provision of appropriate care. Accessing ANC services presented particular challenges, with health care workers sometimes denying all clinic services to women who were not accompanied by husbands. Several participants reported being denied care until delivery. The difficulties participants reported in accessing health care services as both sex workers and unmarried women have potential social and health consequences in light of the high levels of HIV and STIs among FSWs in sub‐Saharan Africa.